Responsibility as a consolidation factor in the urban community of the Russian border region - V. P. Babintsev; G. N. Gaidukova; Zh. A. Shapoval (RUDN journal of Sociology)
Responsibility (social) is one of the most important value bases for consolidation of communities of different levels. Only if it is established in the mass consciousness as a personal essential quality, consolidation can become real. Despite the long-standing tradition of discussing responsibility, it still seems undeveloped in social-humanitarian knowledge. In addition, insufficient individual and collective responsibility often determines the life of communities of different levels and hinders unification. The article aims at assessing the role of personal responsibility in the consolidation of the urban population in the border region. This aim is determined not only by the significance of the responsibility pattern for consolidation but also by the special situation in the frontier region, which is influenced by the special military operation in Ukraine, i.e., responsibility acquires existential significance. The article is based on the results of the authors’ sociological study conducted in 2022-2023 using the survey of urban residents in the Belgorod, Kursk and Voronezh Regions, expert survey and focus groups. The study showed the ambiguity and even paradoxical nature of common judgments regarding the extent of responsibility for oneself and society. The first paradox is the contradiction between the relatively high symbolic significance of the attitude towards socially responsible behavior and the inability to realize it. The second paradox is manifested in the conflict between individualistic and collectively oriented behavioral models: most urban residents worry about the situation in their “location”, about others and loved ones, but at the same time almost two-thirds agree that a person is responsible only for oneself and one’s actions. The third paradox is that contrary to widespread stereotypes about the predominantly individualistic orientation of the youth the share of young people who believe that a person is responsible only for oneself turned out to be lower than in other age groups.